2022
DOI: 10.1097/md.0000000000028777
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion for diarrhea in COVID-19

Abstract: Background:Coronavirus disease 2019 (COVID-19) is an acute respiratory infectious disease that is often accompanied by diarrhea, patients with symptoms such as diarrhea are more likely to develop severe pneumonia, while diarrhea is the most prominent among atypical symptoms. The incidence of diarrhea in COVID-19 patients is 2.0% to 49.5%. Moxibustion has been proven to have a therapeutic effect on diarrhea; however, there is no high-quality evidence on moxibustion for diarrhea in COVID-19 patients. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some researchers have explored the safety and effectiveness of acupuncture in the treatment of patients with long COVID through systematic reviews and meta-analyses based on the related symptoms of long COVID [114] . At present, some researchers are planning to further explore acupoint stimulation therapy for patients with long COVID, and design research programs that can generate higher-level evidence involving improvements in taste abnormalities [115] , anorexia [116] , functional dyspepsia [74] , diarrhea [18] and other symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have explored the safety and effectiveness of acupuncture in the treatment of patients with long COVID through systematic reviews and meta-analyses based on the related symptoms of long COVID [114] . At present, some researchers are planning to further explore acupoint stimulation therapy for patients with long COVID, and design research programs that can generate higher-level evidence involving improvements in taste abnormalities [115] , anorexia [116] , functional dyspepsia [74] , diarrhea [18] and other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In classical traditional Chinese medicine (TCM) therapy, acupoint stimulation has a virtuous regulatory effect on the body through invasive or non-invasive stimulation of specific acupoints, including various forms of stimulation, such as manual acupuncture (MA) [16] , electroacupuncture (EA) [17] , and moxibustion [18] . Since ancient times, there has been an accumulation of experience in the prevention and control of infectious diseases using acupoint stimulation therapy [19] .…”
Section: Introductionmentioning
confidence: 99%
“…[15] The results of Shi et al indicated SAAT with Shenhuang plaster reshaped the composition of the microbiota, especially butyrate-producing gut bacterium, and promotes intestinal peristalsis, and the combination of paclitaxel with Shenhuang SAAT exerted potent immunostimulatory effects. [23] At present, there have been several studies applying SAAT or other forms of acupuncture to the remission of coronavirus disease 2019-related symptoms, including headache, [46] diarrhea, [47] and fatigue. [48] Whereas, few studies have focused on the mechanisms underlying the prophylactic effect of SAAT.…”
Section: Groupmentioning
confidence: 99%